1997
DOI: 10.1007/bf01999568
|View full text |Cite
|
Sign up to set email alerts
|

Lead, cadmium, and selenium in the blood of patients with sporadic amyotrophic lateral sclerosis

Abstract: We determined whole blood lead and cadmium levels, and serum selenium levels in patients with sporadic amyotrophic lateral sclerosis and age- and sex-matched controls. Disability due to the disease directly correlated with lead levels, and there was a strong inverse correlation with selenium concentrations. Lead and selenium concentrations tended to be similar in the cases and controls, both in the study population as a whole and after the removal from the analysis of the patients with the highest degree of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 31 publications
3
36
0
1
Order By: Relevance
“…Consistent with previous data, Vinceti et al [17] found no abnormalities in whole blood lead levels during early stages of the disease. However, they noted a positive correlation between whole blood lead levels and the progression of the disease, measured in this case by worsening functional impairment.…”
Section: Leadsupporting
confidence: 82%
“…Consistent with previous data, Vinceti et al [17] found no abnormalities in whole blood lead levels during early stages of the disease. However, they noted a positive correlation between whole blood lead levels and the progression of the disease, measured in this case by worsening functional impairment.…”
Section: Leadsupporting
confidence: 82%
“…Among the metals analyzed, Pb resulted higher in patients' than in controls' group. Much evidence in the literature describes Pb as a neurotoxic agent and as being related to ALS [22,23], since high levels of this metal have been found both in blood and in cerebrospinal fluid of ALS patients [24,25]. In our analyses, Pb levels were twice higher in ALS subjects than in controls, supporting the hypothesis of a possible involvement of this metal in the etiology of the disease.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Wistar rats developed peripheral polyneuropathy after long-term exposure to Cd 2+ from drinking water (Sato et al, 1978). In humans, Cd 2+ concentrations are significantly elevated in the brains of AD (Lui et al, 1990) and ALS (Vinceti et al, 1997) patients. Also, occupational exposure to Cd 2+ increases the risk of AD (Bar-Sela et al, 2001), ALS, and brain atrophy (Bar-Sela et al, 1992).…”
Section: Discussionmentioning
confidence: 99%